2022
DOI: 10.1177/09603271211063161
|View full text |Cite
|
Sign up to set email alerts
|

Methylation patterns of the CDKN2B and CDKN2A genes in an indigenous population exposed to pesticides

Abstract: The INK4 -ARF locus includes the CDKN2B and CDKN2A genes and is functionally relevant in the regulation of both cell proliferation and senescence. Studies have reported modifications of DNA methylation in this locus by exposure to environmental contaminants including pesticides; however, until now, specific methylation profiles have not been reported in genetically conserved populations exposed to occupational pesticides. The aim of this study was to determine the methylation profiles of the CDKN2B and CDKN2A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…CDKN2B hypomethylation was observed in exposed individuals, with a signification association between methylation and exposure levels, while hypermethylation of the CDKN2A promoter was observed in moderately-exposed individuals. Finally, Paredes-Céspedes et al ( 68 ), determined methylation profiles of the CDKN2B and CDKN2A genes in a genetically conserved population exposed to pesticides. They observed that the farmer group presented a higher methylation percentage of CDKN2B than the non-farmer group, but no differences in CDKN2A were observed between groups.…”
Section: Resultsmentioning
confidence: 99%
“…CDKN2B hypomethylation was observed in exposed individuals, with a signification association between methylation and exposure levels, while hypermethylation of the CDKN2A promoter was observed in moderately-exposed individuals. Finally, Paredes-Céspedes et al ( 68 ), determined methylation profiles of the CDKN2B and CDKN2A genes in a genetically conserved population exposed to pesticides. They observed that the farmer group presented a higher methylation percentage of CDKN2B than the non-farmer group, but no differences in CDKN2A were observed between groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a more complete approach combining urinary pesticide residue determination and epigenomic investigation, indigenous Huichol farmers in Mexico occupationally exposed to organophosphate pesticides were assessed by methylation profiling of CDKN2A and CDKN2B genes, alongside the determination of six general metabolites of organophosphates in urine samples. The study encompassed 160 farmers and 30 non-farmers with similar levels of DAPs in both, indicating that the primary source of contamination stemmed from their living environment or ingested food ( 164 ).…”
Section: Applicationsmentioning
confidence: 99%
“…For example, variations in dermal polymorphisms of the FLG gene, responsible for encoding the filaggrin protein, can have significant implications ( 147 , 167 ). Thus, epigenomic assessments, such as studies on gene methylation, also offer promise as a valuable tool in human biomonitoring, offering reduced variability in assessments, as in the correlation between the CpG site of the CDKN2B gene and work time in farmers ( 164 ). Furthermore, occupational pesticide exposure has been extensively linked to genomic instability and other genetic and epigenetics aspects ( 273 ).…”
Section: Synthesis and Future Directionsmentioning
confidence: 99%